EFEITO DE Vismia guianensis (Aubl.) Chosy EM MODELO DE SEPSE LETAL INDUZIDA POR Candida albicans. - COSTA, Arthur André Castro da (2021)
Candida albicans is an opportunistic fungus responsible for local or systemic infections such as sepsis. The main treatment for fungal sepsis includes the use of Fluconazole or Amphotericin B. However, resistance and adverse reactions to these drugs serve as an argument for the search for alternative treatments, including, among them, the plant species. In this context, Vismia guianensis (Aubl.) Chosy, a plant popularly known as “pau-de-lacre”, has antifungal action already proven in vitro, but its in vivo effect is still little explored. Thus, this work aimed to evaluate the effect of V. guianensis on lethal infection induced by Candida albicans. The anti- Candida effect of the hydroethanolic extract of the V. guianensis leaves (EHVG) and Anthraquione (one of the major compounds of EHVG) was evaluate in Tenebrio molitor larvae and Swiss mice. The T. molitor larvae were divided into 4 groups: Control, ANFO B, EHVG and Anthraquione for evaluation of acute toxicity and to determine the dose to be used in lethal infection in mice. Treatments and infection occurred by intracellomic route. To determine the EHVG effect on T. molitor survival the larvae were lethally infected with C. albicans (5x105 CFU/mL) and just after treated according the following groups: Control: infected and untreated, ANFO B: Infected and treated with Amphotericin; EHVG: infected and treated with the extract, and Anthraquione: infected and treated with this chemical compound. For other evaluations the T. molitor larvae distributed in the same groups of received a sublethal inoculum (5x104 CFU/mL). For mouse trials, the animals were immunosuppressed with cyclophosphamide [50mg/kg, intraperitoneally (ip.)], 48 hours before infection, and the for the lethal infection they received blastoconids of C. albicans (6x107 CFU, via ip.) and evaluated for 7 days. The immunological evaluation occurred in groups infected with a sublethal inoculum (2x107 CFU, via ip.) For the evaluations male Swiss mice were distributed in the following groups: CONTROL: Infected and untreated; ANFO B: animals infected and treated with Amphotericin B (600μg/Kg, via ip.) and EHVG: infected and treated with the extract, (5mg/Kg, orally), and SHAM: uninfected and untreated. The results showed that EHVG at the highest dose (100mg/kg) was toxic to 60% in larvae, but the treatment with low doses of EHVG (5mg/kg) increased survival of T. molitor larvae with an effect like Amphoterecin B. In this assay treatment with Anthraquione was less effective than EHVG. The treatment with EHVG reduced the sub-lethal infection confirming the antifungal effect of this extract as previously described in vitro. This antifungal effect may be due to the presence of more than one compound present in the extract. Treatment with EHVG also increased survival (60%) and the life expectancy in mice, possibly because it reduced the number of CFU in the blood and peritoneum. Treatment with EHVG also increased total number of blood leukocytes, mainly neutrophils. In the peritoneum the treatment EHVG increased the recruitment of macrophages. Altogether these results indicate that EHVG presents antifungal action and immunomodulatory effect able to improve the survival of invertebrate or vertebrate animals infected with C. albicans. The beneficial effects of EHVG on lethal sepsis are related to the presence of a phytocomplex formed by compounds present in the extract possibly related to the presence of Anthraquinone in association with Vismione, Catechin and Kaempferol.